PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID UNTUK MOTIVASI SISWA SMP MUHAMMADIYAH CIANJUR - Nani Kustini; Dirgantara Wicaksono (Media Riset Bisnis Manajemen Akuntansi, 2025)
This study aims to develop a valid, practical, and effective Android-based social studies learning media using Articulate Storyline to increase the learning motivation of 8th-grade students at SMP Muhammadiyah Cianjur. Conventional learning methods have been observed to be teacher-centered and lack technological integration, causing boredom and low student motivation. This research uses the Research and Development (RD) method with the ASSURE model (Analyze, State, Select, Utilize, Require, Evaluate/Revise). Data were collected through expert validation questionnaires, student response questionnaires, and pre-test/post-test. The results showed that the developed media was declared "very feasible" by media experts (88% score) and material experts (97.33% score). The media also proved effective in significantly increasing student learning outcomes, with the average post-test score (76.83) being much higher than the pre-test score (55.08), resulting in a medium category N-Gain score of 0.485. It is concluded that the Android-based interactive media is feasible and effective for improving student learning motivation and outcomes in social studies.Keywords : Articulate Storyline, Learning Media, Learning Motivation, Social Studies